Clinical mycology \ - Dismukes, William E.; Pappas, Peter G.; Sobel, Jack D. (Oxford ; New York : Oxford University Press, 2003)
Within the field of infectious diseases, medical mycology has experienced significant growth over the last decade. Invasive fungal infections have been increasing in many patient populations, including: those with AIDS; transplant recipients; and the elderly. As these populations grow, so does the diversity of fungal pathogens. Paralleling this development, there have been recent launches of several new antifungal drugs and therapies. Clinical Mycology offers a comprehensive review of this discipline. Organized by types of fungi, this volume covers microbiologic, epidemiologic and demographic aspects of fungal infections as well as diagnostic, clinical, therapeutic, and preventive approaches. Special patient populations are also detailed.
Intro -- Contents -- Contributors -- PART I: INTRODUCTION -- 1. Laboratory Aspects of Medical Mycology -- 2. Epidemiology of Systemic Fungal Diseases: Overview -- PART II: SYSTEMIC ANTIFUNGAL DRUGS -- 3. Amphotericin B -- 4. Liposomal Nystatin -- 5. Flucytosine -- 6. Azole Antifungal Drugs -- 7. Cell Wall Synthesis Inhibitors: Echinocandins and Nikkomycins -- 8. Terbinafine -- 9. Resistance to Antifungal Drugs -- 10. Adjunctive Antifungal Therapy -- PART III: MYCOSES CAUSED BY YEASTS -- 11. Candidiasis -- 12. Cryptococcosis -- 13. Rhodotorula, Malassezia, Trichosporon, and Other Yeast-Like Fungi -- PART IV: MYCOSES CAUSED BY MOULDS -- 14. Aspergillosis -- 15. Zygomycoses -- 16. Hyalohyphomycoses (other than Aspergillosis and Penicilliosis) -- 17. Phaeohyphomycoses -- PART V: MYCOSES CAUSED BY DIMORPHIC FUNGI -- 18. Histoplasmosis -- 19. Blastomycosis -- 20. Coccidioidomycosis -- 21. Paracoccidioidomycosis -- 22. Sporotrichosis -- 23. Penicilliosis -- PART VI: MYCOLOGY INVOLVING SKIN AND SUBCUTANEOUS TISSUES -- 24. Superficial Cutaneous Fungal Infections -- 25. Eumycetoma -- 26. Chromoblastomycosis -- PART VII: OTHER MYCOSES -- 27. Pneumocystosis -- 28. Miscellaneous Fungi -- PART VIII: SPECIAL PATIENT POPULATIONS -- 29. Fungal Infections in Neutropenic Patients -- 30. Fungal Infections in Blood or Marrow Transplant Recipients -- 31. Fungal Infections in Solid Organ Transplant Recipients -- 32. Fungal Infections among Patients with AIDS -- Index.
Bibliographic Level Mode of Issuance: Monograph
Includes bibliographical references and index.
English
Description based on publisher supplied metadata and other sources.
Keywords: Medical mycology; Electronic books